Improving the quality of recorded mbone sessions using a distributed model - Lambrinos, Lambros; Kirstein, Peter; Hardman, Vicky (My University, 1999)
Multicast conference recording currently uses a single, arbitrarily placed recorder. The recordings have less than perfect quality because they are often not loss-free, and the recording is as perceived by the recorder (delays from senders to the recorder have been imposed on the streams). An ultimate recording consists of the loss-free data set, extra information about loss patterns received by individual participants, and information about the delays between participants. The delay information is required so that we can re-create the conference from a number of perception points. In this paper, we initially consider off-line recording of material, which produces loss-free recording, can provide timing information, and is simple, but does suffer from deficiencies. Our second (and preferred) solution uses a distributed arrangement of a number of co-operating recording caches, and sender interaction far local repair.
Keywords: Clouds; Applications; Distributed simulation